A Proposal to Extend Brodmann's Areas Concept to a New Model - Düzgün, Aysel; Güntekin, Bahar; BAŞAR, EROL (Anka Publisher, 116-11 Sok No.10 K 2 D 2, Bornova, Izmir 35050, Turkey, 2014)
Since the beginning of the last century, the localization of brain function is presented by Brodmann areas, or maps that are a result of anatomic organization. They are used in order to give a global idea of cortical structures for given sensory cognitive functions. In the last decades, the analysis of brain oscillations gained high importance for the correlation of brain functions. Moreover, the use of the spectral connectivity provides information on dynamic connectivity between various structures. Beside this, according to (Luria, 1966), brain responses have dynamic features and structural localization is almost impossible. According to these uses, brain functions are very difficult to localize and need joint analysis of oscillation and event related coherences. In the present report, a model called "CLAIR" is described to extend and possibly to replace the concept of the Brodmann areas. To design a perfect functioning CLAIR model requires years; however, the beginning step is provided in the present report.
Keywords: Brodmann; EEG; Oscillations; Functional Map; CLAIR